“The Butterfly” An Applied Theatre Performance about Hopes and Dreams of Myanmar Youth aimed at Exchanging Perceptions of Thai People about the Identity of the Myanmar Youth in Thailand, as Part of Myanmar Up Close at Museum Siam - สุรัสวดี ปวลักขิ์ (Journal of Fine and Applied Arts Khon Kaen University, 2018)
Myanmar Up Close program held at Museum Sian from April to July, 2016 was aimed at eliminating the ethnic bias of Thai people and society towards Myanmar migrant workers in Thailand. The youth performance “The Butterfly” was one of the learning programs in the Myanmar Up Close exhibition telling stories about Myanmar Youth in Mahachai district, Samut-sakorn province. The applied theatre process “The Butterfly” was a participation process between the director and the actors in order to search for and develop stories from Myanmar youths. The theatre in education process empowered the youth actors. Also it incorporated inter-relationship between the youth actors and the audiences as this process would eradicate bias of Thai audiences towards Myanmar migrant workers in Thailand.